2011
DOI: 10.1089/jwh.2010.2081
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of the Non-pneumatic Anti-shock Garment on Delays in Accessing Care for Postpartum and Postabortion Hemorrhage in Egypt and Nigeria

Abstract: Background: We examined whether the non-pneumatic anti-shock garment (NASG) ameliorates the effects of delays in transport to and treatment at hospitals for women with postpartum hemorrhage (PPH) and postabortion hemorrhage (PAH) and investigated the effects of NASG use on timing of delivery of interventions inhospital. Methods: Pre=post studies of the NASG were conducted at hospitals in Cairo (n ¼ 349 women), Assuit (n ¼ 274), Southern Nigeria (n ¼ 57), and Northern Nigeria (n ¼ 124). In post-hoc analyses, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…It also compresses the diameter of pelvic blood vessels, thus decreasing blood flow [33]. In preliminary pre‐intervention/intervention trials in tertiary facilities in Egypt and Nigeria, the NASG was shown to significantly improve shock [34], decrease blood loss, reduce emergency hysterectomy for atony, and decrease maternal mortality and severe maternal morbidities associated with obstetric hemorrhage [35,36]. A definitive trial of the NASG for use prior to transport from lower‐level facilities to tertiary facilities is currently underway in Zambia and Zimbabwe.…”
Section: Treatment Of Postpartum Hemorrhagementioning
confidence: 99%
“…It also compresses the diameter of pelvic blood vessels, thus decreasing blood flow [33]. In preliminary pre‐intervention/intervention trials in tertiary facilities in Egypt and Nigeria, the NASG was shown to significantly improve shock [34], decrease blood loss, reduce emergency hysterectomy for atony, and decrease maternal mortality and severe maternal morbidities associated with obstetric hemorrhage [35,36]. A definitive trial of the NASG for use prior to transport from lower‐level facilities to tertiary facilities is currently underway in Zambia and Zimbabwe.…”
Section: Treatment Of Postpartum Hemorrhagementioning
confidence: 99%
“…5 This is to say that postpartum hemorrhage is a major threat to maternal health and a myth to achievement of millennium development goal 5 of improving maternal health. 6 Nevertheless, these are unnecessary deaths that can be prevented and one way of preventing these deaths is by the use of the Non-pneumatic anti shock garment (NASG) which is low technology first aid device that can be placed around the lower body of a woman who has gone in to shock from obstetric bleeding. This garment decreases blood loss, recovers women from shock and keeps them alive while awaiting treatment According Miller et al, the NASG is a low-technology pressure device that decreases blood loss, restores vital signs, and has the potential to improve adverse outcomes by helping women survive delays in receiving adequate emergency obstetric care.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The non-pneumatic anti-shock garment (NASG) is a firstaid device that can save lives of women experiencing obstetric hemorrhage from any aetiology. 10 The use of the NASG reportedly addresses the immediate lifethreatening complication by reversing hypovolemic shock among mothers having shock due to PPH and returns blood to the heart, lungs, and brain by applying pressure to the lower body and abdomen. 11 The use of an NASG can stabilize a patient while awaiting transport, during transport, or during delays in receiving care at referral facilities.…”
mentioning
confidence: 99%